Giving Free English Lessons and Vocabulary Modules: Learning Beyond the Classroom Walls Through A Community Service Program - Anna Marietta da Silva; Aditya Pradipta; Vina Yuliana; Marcella Sonya Maria; Guida Paradita (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
The community service aims at providing free English lessons and English vocabulary learning modules to grade 3 and 4 students in one learning community in Duren Sawit East Jakarta through a six-week teaching program that is integrated with one subject offered in the Master Program of Applied English Linguistics at Atma Jaya Catholic University of Indonesia. Ten master students became the voluntary teachers (together with other volunteers). The program is a continuation of a similar program held from January to June 2019 by the first author. The student-teachers used a variety of learning approaches and methods that are predicted to suit the students’ needs. They identified that different groups of students required different approaches, materials, and activities in order to learn English enjoyably. It is suggested that future teacher volunteers use the ready-made modules as a basis of their teaching and continually adjust them based on the students’ needs. Another recommendation is the scaffolding-based learning method and the sustenance of the English program that appreciates the cultural, social and linguistic assets students brought to the class.